Impacts of a ‘Double Disaster’ on Small-Scale Grouper Farmers in the Bicol Region, Philippines - Preña, Emmanuel M.; Labayo, Cherrylyn P. (Philippine Social Science Journal, 2022)
The series of devastating typhoons during the COVID-19 pandemic was a remarkable event in the Philippines’ history of natural disasters. This case study documented the impacts of the two overlapping shock events on the livelihood of small-scale grouper farmers in the towns of Ragay and Del Gallego, Camarines Sur, Philippines, while reflecting on their coping strategies and social support. The findings revealed that the typhoons induced additional pressure on the well-being of the farmers while they were still dealing with the negative impacts of the pandemic. The contributing aspects to their livelihood vulnerability were attributed to their limited adaptive capacity to withstand various shocks and the susceptibility of their farm sites to repeated natural hazards. The study also identified different coping strategies the farmers undertook, including the roles of social support, in dealing with the impacts of these shocks. Establishing anticipatory action protocols is necessary to manage the long-term impact of repeated shocks to strengthen their livelihood and household resilience.